Case anxiety and its relationship to skillful achievement using the sign tool for second-stage female students at the College of Physical Education and Sports Sciences (Journal of the College of Basic Education, 2022)
Search Title: trait anxiety and relationship to the collection tool pillar skills among students of the second phase of Physical Education and Sports Science Departmentresearch goals: -identify the characteristic concern among students of the second phase of the Department of Physical Education and Sports Scienceidentify the relationship of trait anxiety achievement skills among students with a tool pillar second phase imposing Search:The existence of a statistically significant relationship between trait anxiety and learning skills among students with a tool pillar second phaseResearch Methodology: The researcher used the descriptive approach is not appropriate for the proceedings of this study.The research sample: The study sample consisted of 20 female students from the second stage in the Department of Physical Education and Sports Science Faculty of Basic Education and has been used trait anxiety scaleResults of the study: The study showed the following results:Alastnajat:1-trait anxiety that the percentage of the female students in the second phase were highThere are no correlation between educational skill and trait anxiety when students relationshipRecommendations:1-focus and attention to psychological preparation programs that affect the performance of the players.The need to create and set up training programs that serve the psychological preparation of the players, especially in a game of rhythmic gymnastics.3-need sustained attention from the coaches to the sports anxiety levels that accompany the players during the lesson and direct manner that Akhaddmhn to achieve better performance